Dynamic Roles of microRNAs in Neurogenesis - Lang, Ming-Fei; Shi, Yanhong (Frontiers in Neuroscience, 2012)
MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression at the post-transcriptional level by mediating mRNA degradation or translational inhibition. MiRNAs are implicated in many biological functions, including neurogenesis. It has been shown that miRNAs regulate multiple steps of neurogenesis, from neural stem cell proliferation to neuronal differentiation and maturation. MiRNAs execute their functions in a dynamic and context-dependent manner by targeting diverse downstream target genes, from transcriptional factors to epigenetic regulators. Identifying context-specific target genes is instrumental for understanding the roles that miRNAs play in neurogenesis. This review summarizes our current state of knowledge on the dynamic roles that miRNAs play in neural stem cells and neurogenesis.